1977
DOI: 10.1111/j.1467-842x.1977.tb01108.x
|View full text |Cite
|
Sign up to set email alerts
|

A self–administered questionnaire for detection of unrecognised coronary heart disease

Abstract: On an individual and a population basis, an increased incidence of coronary heart disease is associated with classical cardiovascular risk factors, but many cases occur in people not identified as at high risk. Conversely, many people at high statistical risk do not develop coronary disease. We used a questionnaire to identify unrecognised coronary heart disease in people attending large-scale health survey centres. Participants were required to report the presence and characteristics of any chest pain. Those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Other surveys have also indicated that many women are unaware that they have symptoms of early heart disease or that they possess risk factors for developing CVD. [6][7][8] Legato et al 9 reported that 44% of women in the United States surveyed believed that it was somewhat or very unlikely that they would suffer a heart attack, and 58% believed they were as likely or more likely to die of breast cancer than heart disease; yet 74% of these women rated themselves as fairly or very knowledgeable. Of those women who saw a physician regularly, 59% reported that their physician never spoke to them about heart disease, including 44% of women 60 years or older.…”
Section: For Editorial Comment See Page 516mentioning
confidence: 99%
“…Other surveys have also indicated that many women are unaware that they have symptoms of early heart disease or that they possess risk factors for developing CVD. [6][7][8] Legato et al 9 reported that 44% of women in the United States surveyed believed that it was somewhat or very unlikely that they would suffer a heart attack, and 58% believed they were as likely or more likely to die of breast cancer than heart disease; yet 74% of these women rated themselves as fairly or very knowledgeable. Of those women who saw a physician regularly, 59% reported that their physician never spoke to them about heart disease, including 44% of women 60 years or older.…”
Section: For Editorial Comment See Page 516mentioning
confidence: 99%